SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN LAPTOP DAN KOMPUTER BERBASIS WEBSITE MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS DAN WEIGHTED PRODUCT - Renaldy Cahya; Bagus Mulyawan; Tri Sutrisno (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
The development of science and technology is now increasingly advanced and increasing rapidly, the use of laptops in the present times that are needed for everyday needs. Many choices of laptops and computers available on the market make people difficult to make choices. People usually only consider prices without regard to specifications. Analytical Hierarchy Process method is one method to help the calculation of selection criteria and Weighted Product methods to facilitate the community in choosing laptops and computers by ranking. The way it works is that the user chooses the 5 criteria provided, namely price, processor, ram, hdd, vga after choosing according to needs, the 10 best laptop ranking will appear based on the user's selection.